Variación del patrón reproductivo de dos poblaciones mexicanas de Artemia franciscana (Branchiopoda: Anostraca) y su comparación con la población de Babía de San Francisco, California - Castro Mejía, J.; Malpica Sánchez, A.; Castro Mejía, G.; Castro Barreray, T.; Lara Andrade, R. De (Revista de Biología Tropical, 1999)
The reproductive characteristics of the populations of A. franciscana of Yavaros, Sonora; Bahía de Ceuta, Sinaloa, and San Francisco Bay, California U.S.A.were obtained in controlled conditions (salinity and temperature) and the following data were collected: length of male and female adults; width of abdomen and ovigerous sac; prereproductive, reproductive and postreproductive period; numher and frequency per broods. and number and percentage of the offspring produced per brood per female. San Francisco adults were larger and wider than those of Yavaros or Bahía de Ceuta. The total reproductive period was 43.6 days in Yavaros females and 29.7 days in Bahía de Ceuta. The number of broods was 5 for Yavaros and 3 for Ceuta as opposed to 14 for those of San Francisco. The period between broods was 4 days on average for the three populations. Thc average output of Yavaros was of 74 nauplii and 10 cysts/brood/female: for Bahía de Ceuta it was 22 nauplii and 5 cysts/brood/female. Output increased when both populations were eros sed with males from San Francísco Bay; the females of Yavaros had 400 nauplii per brood and the females of Bahía de Ceuta yielded 46 cysts per brood. These increases in production are attributed lo the greater intensily in courtship being in proportíon to the size of the males. San Francisco males, being larger, exhibít a greater intensity in courtship cven when females are smaller.